Thermal Performance Assessment of a Novel Hybrid Reactor for Solar Thermochemical Processes - Atthawit Saengpradab; Jirayut Tathong; Hattakit Kongsrichay; Srirat Chuayboon; Stéphane Abanades (SolarPACES Conference Proceedings, 2024)
Solar thermochemical conversion processes offer a promising pathway for converting sunlight into clean, sustainable, and carbon-neutral fuels. A solar chemical reactor is one of the most essential components that utilizes concentrated solar energy to drive chemical reactions. In this study, a novel hybrid solar reactor is designed, fabricated, and tested to assess its thermal performance for the purpose of studying the solar thermochemical conversion processes in Thailand for the first time. It was performed under different heating modes regarding solar heat and/or electrical heat, with the aim to support day-and-night operation and variations in solar radiation conditions. The reactor was experimentally tested under on-sun, off-sun, and hybrid conditions using air as a heat transfer fluid. As a result, with one kWth solar thermal power input absorbed, the solar reactor achieved high temperatures exceeding 500 °C from the hybrid system while the reactor absorption efficiency was found to be 4%. The reactor demonstrated the possibility and reliability of performing solar thermochemical conversion processes under day-and-night and unstable solar radiation conditions.